2000
DOI: 10.1016/s0006-3495(00)76545-3
|View full text |Cite
|
Sign up to set email alerts
|

Heme Structure and Orientation in Single Monolayers of Cytochrome c on Polar and Nonpolar Soft Surfaces

Abstract: Polarized x-ray absorption fine structure (XAFS) spectroscopy has been performed in fluorescence mode under total external reflection conditions on frozen hydrated single monolayers of yeast cytochrome c (YCC). The protein molecules were vectorially oriented within the monolayer by tethering their naturally occurring and unique surface cysteine residues to the sulfhydryl-endgroups at the surface of a mixed organic self-assembled monolayer, itself covalently attached to an ultrapure silicon wafer. The sulfhydry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 40 publications
1
24
1
Order By: Relevance
“…Expectedly we find that, due to the approximate C 2 -symmetries in the models used, a clear-cut discrimination between symmetry-related angles [Eqs. (18), (19) (20)- (22):…”
Section: IIImentioning
confidence: 99%
“…Expectedly we find that, due to the approximate C 2 -symmetries in the models used, a clear-cut discrimination between symmetry-related angles [Eqs. (18), (19) (20)- (22):…”
Section: IIImentioning
confidence: 99%
“…Equation [9] can be used to give an estimate of the depth of immersion of a fluorescent chromophore in a nonconductive matrix using experimentally measured values of the ratio k q d /k q k and known or estimated values for the lifetime of the encounter complex, c , and the parameter ␤.…”
Section: Depth Of Immersion Of a Chromophorementioning
confidence: 99%
“…Values of depth of chromophore immersion (R 0 Ϫ r V ) for different quenching mechanisms, calculated using Eq. [9] with an experimental ratio (k q d /␣ 0 k q (I)) and a lifetime of the encounter complex, c ϭ 3 ϫ 10 Ϫ10 s, are also presented in Table 2. As shown in the table, (R 0 Ϫ r V ) Ͼ 6 Å and Ͼ7.0 Å for ICHA and ET quenching mechanisms, respectively.…”
Section: Immobilized Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] The properties of vectorially orientated YCC, chemisorbed via Cys102 at thiol-modified surfaces, have been extensively studied. [30][31][32][33] Scanning probe microscopy has shown that YCC can be immobilized directly on gold via Cys102. [34][35][36] Moreover, we have shown that YCC, vectorially chemisorbed on gold, exhibits very fast, reversible interfacial electron transfer and retains its native functionality, that is, the ability to interact with redox enzymes in solution.…”
Section: Introductionmentioning
confidence: 99%